2011
DOI: 10.1002/adem.201100013
|View full text |Cite
|
Sign up to set email alerts
|

Free‐Standing Patterned Ceramic Structures Obtained by Soft Micromolding

Abstract: Patterned ceramic films with constant thickness can be processed by a soft lithographic method. By using micromolding in capillaries, the slurry is forced to flow through channels created in an elastomer stamp. After drying, layers deposited on an amorphous carbon substrate were sintered under inert atmosphere. Free‐standing ceramic structures with high aspect ratio were obtained with lateral resolution better than 1 µm. Dimensional changes were monitored in comparison to films deposited on stiff sapphire subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…For the stamp fabrication, the film structure was first transferred from the CAD file to a gold/chrome mask by electron beam lithography, similarly to the process applied by Seils et al . 22. This mask was subsequently used to transfer the pattern onto a silicon wafer (Ø 100 mm) coated with a 16 µm thick cured negative photoresist (SU‐8, Microchem Corp, Newton, MA) using X‐ray photolithography 22.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the stamp fabrication, the film structure was first transferred from the CAD file to a gold/chrome mask by electron beam lithography, similarly to the process applied by Seils et al . 22. This mask was subsequently used to transfer the pattern onto a silicon wafer (Ø 100 mm) coated with a 16 µm thick cured negative photoresist (SU‐8, Microchem Corp, Newton, MA) using X‐ray photolithography 22.…”
Section: Methodsmentioning
confidence: 99%
“…After drying, removal of the stamp and firing, stable functional patterns are produced 21. When controlling the adhesion of the sintering layer to the substrate, it is also possible to fabricate free‐standing foils 22. In addition, by using larger amounts of slurry, ceramic layers or bodies with a structured surface at the micrometric scale can be obtained 23.…”
mentioning
confidence: 99%
“…Finally, the results of the simulations are compared with measurements. The green ceramic stripes used for the experiments were manufactured using soft micromolding in capillaries (MIMIC), a method that allows producing patterned structures at small scales with relatively high aspect ratios and accuracies …”
Section: Introductionmentioning
confidence: 99%
“…[7,19] Overviews of general nano-and micropatterning techniques were given by Xia and Whitesides, [20] Heule et al, [21] and ten Elshof et al [22] Ceramic patterning methods in particular were compared by Martin and Aksay [23] and by Holthaus et al [24] Seils et al [19] reported recently synthesis of non-deforming free standing ceramic films. [7,19] Overviews of general nano-and micropatterning techniques were given by Xia and Whitesides, [20] Heule et al, [21] and ten Elshof et al [22] Ceramic patterning methods in particular were compared by Martin and Aksay [23] and by Holthaus et al [24] Seils et al [19] reported recently synthesis of non-deforming free standing ceramic films.…”
mentioning
confidence: 99%
“…Free standing ceramic bodies and masks have been recently reported for tetragonal zirconia stabilized with 3 mol% yttria (Y-TZP) and alumina. [7,19] Overviews of general nano-and micropatterning techniques were given by Xia and Whitesides, [20] Heule et al, [21] and ten Elshof et al [22] Ceramic patterning methods in particular were compared by Martin and Aksay [23] and by Holthaus et al [24] Seils et al [19] reported recently synthesis of non-deforming free standing ceramic films. We adapt micromolding in capillaries (MIMIC) and embossing [25] for creating free standing ceramic foils and masks.…”
mentioning
confidence: 99%